Beta-cell function in type 2 diabetic patients who failed to maintain good glycemic status with a combination of maximum dosages of metformin and sulfonylurea - Kunavisarut T (Dove Medical Press, 2019)
Tada Kunavisarut, Sutin Sriussadaporn, Raweewan LertwattanarakDivision of Endocrinology and Metabolism, Siriraj Hospital, Mahidol University, Bangkok, ThailandBackground: The aim of this study was to investigate beta-cell function and examine whether sulfonylureas (SUs) are still useful in patients with type 2 diabetes (T2DM) who failed to maintain optimal glycemic control with a combination of maximum dosages of metformin and SU.Method: T2DM who had HbA1c >8% during treatment with a combination of maximum dosages of metformin and SU were studied. After enrollment, the patients were assigned to continue maximum dosages of SU and metformin for 2 weeks and then underwent the first oral glucose tolerance test (OGTT), the Max-SU OGTT. After the Max-SU OGTT, SUs were discontinued for 4 weeks and the second OGTT, the Discont-SU OGTT, was performed. After the Discont-SU OGTT, the same SU was restarted at 25% of the maximum dosage (25%Max-SU). After taking 25%Max-SU for 4 weeks, the third OGTT, the 25%Max-SU OGTT, was performed. Metformin at the same dosage was continued throughout the study. Normal OGTT (NGT) subjects, matched for age and body mass index (BMI), were also studied.Results: There were 25 T2DM and 28 NGT subjects. There was no difference in age and BMI between the two groups. The beta-cell function during Max-SU was 0.1, which was higher than 0.06 during Discont-SU (p<0.001) and also higher than 0.09 during 25%Max-SU (p=0.269). The beta-cell function during 25%Max-SU was higher than during Discont-SU (p<0.001). The beta-cell function of the NGT group was 0.34 and higher than during Max-SU (p<0.001). Fasting capillary blood glucose (FCBG) levels during Discont-SU (14.2±3.7 mmol/L) were higher than during 25%Max-SU (12.3±3.4 mmol/L) and during Max-SU (10.3±2.4 mmol/L) (p<0.05). In addition, the FCBG during Discont-SU was higher than that during 25%Max-SU (p<0.05).Conclusion: In T2DM patients who failed to achieve glycemic control with a combination of maximum dosages of metformin and SU, the beta-cell function declined compared to NGT subjects. However, the beta-cells were still responsive to SUs, which play a significant role in glycemic control.Keywords: beta-cell function, sulfonylureas, sulfonylurea failure, type 2 diabetes mellitus